Morphological spatial patterns in a reaction diffusion model for metal growth - Benedetto Bozzini; Deborah Lacitignola; Ivonne Sgura (Mathematical Biosciences and Engineering)
In this paper a reaction-diffusion system modelling metal growth processes is considered, to investigate -within the electrodeposition context- the formation of morphological patterns in a finite two-dimensional spatialdomain. Nonlinear dynamics of the system is studied from both the analytical and numerical points of view. Phase-spaceanalysis is provided and initiation of spatial patterns induced by diffusion is shown to occur in a suitable region ofthe parameter space. Investigations aimed at establishing the role of some relevant chemical parameters on stabilityand selection of solutions are also provided. By the numerical approximation of the equations, simulations arepresented which turn out to be in good agreement with experiments for the electrodeposition of Au-Cu and Au-Cu-Cdalloys.